Co-doped porous carbon material derived from Co-Zn bimetallic ZIFs as well as preparation method and application of Co-doped porous carbon material

Through the CO-Zn dual metal ZIFS CO doped porous carbon material, using the catalytic activity sites and carbon nanotimal structures of monocular cobalt and monocular cobalt to solve the problem of low catalytic activity in existing technologies and poor reusable use. It realizes the efficient degradation of chlorampolin and the stability of catalysts.

CN119346154APending Publication Date: 2025-01-24NANJING UNIV OF SCI & TECH
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411547764.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The prior art has problems with low catalytic activity and poor reusability in removing residual chloramphenicol-based antibiotics (CAPs) in the environment, especially when using transition metal-based materials.

Method used

CO-Zn dual-metal ZIFS derived CO doped porous carbon material is used as a catalytic active site by forming single-quality cobalt and monocular cobalt during the burning process, and carbon nanotubes on the surface of the material to enhance the catalytic activity and structural stability sex.

Benefits of technology

It significantly improves the catalytic activity of porous carbon materials for a sulfate, can effectively degrade chloramphenicol, and catalyst has good stability and reuse.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119346154A_ABST
    Figure CN119346154A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of catalysts, and discloses a Co-doped porous carbon material derived from Co-Zn bimetal ZIFs and a preparation method and application of the Co-doped porous carbon material. Elemental cobalt and monatomic cobalt are doped in the porous carbon material; the surface of the porous carbon material is provided with a carbon nanotube. The porous carbon material obtained in the invention has high catalytic activity, and can effectively degrade chloramphenicol.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of catalyst technology, and in particular to a Co-doped porous carbon material derived from Co-Zn bimetallic ZIFs, and a preparation method and application thereof. Background Art

[0002] The increasing number of refractory pollutants in environmental matrices such as antibiotics, chlorine-containing compounds, and personal care products has become a serious global environmental problem. Among them, chloramphenicol antibiotics (CAPs) are a class of broad-spectrum antibiotics. The huge consumption has led to increasingly serious chloramphenicol residues in the environment. The enrichment and accumulation of these highly toxic and biodegradable CAPs and their long-term exposure in the ecological environment will bring hidden and long-term harm to human health and aquatic life. Therefore, the effective removal of CAPs is of great significance for protecting the safety of the ecological environment, and is also of great significance for the health and safety of ordinary people.

[0003] At present, the main treatment technologies for CAPs in water bodies include traditional treatment technologies such as activated sludge method, activated carbon adsorption, membrane filtration, and chemical treatment. In recent years, due to its unique advantages such as high degradation efficiency, strong adaptability and environmental friendliness, researchers at home and abroad have conducted extensive research on persulfate advanced oxidation processes (SR-AOPs). SR-AOPs are effective reaction technologies that chemically oxidize macromolecular organic pollutants into harmless mineralization products through various reactive oxygen species (ROS) (such as sulfate radicals and hydroxyl radicals). During the activation process, the peroxide bond breakage of persulfate (PDS) or peroxymonosulfate (PMS) usually produces these ROS. Therefore, effectively activating PMS to produce more ROS is the key to improving the degradation ability of SR-AOPs. Transition metal-based materials have attracted much attention due to their high PMS activation efficiency and low cost. However, the defects of low catalytic activity and poor reusability caused by the agglomeration of transition metal particles and ion leaching during the reaction still exist.

[0004] Metal-organic frameworks (MOFs), as a class of porous crystalline materials with excellent physicochemical properties, show great potential in constructing advanced heterogeneous catalysts. Since MOFs (such as ZIF-67 (Co), MIL-101 (Fe) and HKUST-1 (Cu)) are generally constructed by self-assembly of transition metal centers and organic ligands, they can be converted into various carbon or transition metal-carbon materials by direct carbonization. Compared with traditional transition metal-carbon materials, this type of MOF-derived materials has the good morphology and high specific surface area of ​​the parent MOFs, stable structure and dispersed metal active sites. However, its ability to catalyze peroxymonosulfate needs to be further improved. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a Co-doped porous carbon material derived from a Co-Zn bimetallic ZIFs, and a preparation method and application thereof. The porous carbon material obtained by the present invention has a strong catalytic effect on peroxymonosulfate, and can degrade residual chloramphenicol by catalyzing peroxymonosulfate to produce active oxygen.

[0006] The invention provides a Co-doped porous carbon material derived from Co-Zn bimetallic ZIFs, wherein the porous carbon material is doped with elemental cobalt and single atomic cobalt; and the surface of the porous carbon material has carbon nanotubes.

[0007] The present invention also provides a method for preparing a Co-doped porous carbon material derived from a Co-Zn bimetallic ZIFs, the preparation method comprising: Step S1: adding a 2-methylimidazole solution to a solution containing cobalt nitrate hexahydrate and zinc nitrate hexahydrate, mixing them evenly, standing them, separating the solid from the liquid, washing them, and drying them to obtain an intermediate product; Step S2: calcining the intermediate product under an inert gas atmosphere to obtain a porous carbon material (Co x Zn 10-x -NC).

[0008] Furthermore, the molar concentration of the 2-methylimidazole solution is 22.05 mmol / 25 mL.

[0009] Furthermore, the preparation method of the 2-methylimidazole solution is specifically as follows: dissolving and dispersing 2-methylimidazole in deionized water.

[0010] Furthermore, based on the cobalt element in the cobalt nitrate hexahydrate and the zinc element in the zinc nitrate hexahydrate, the molar ratio of the cobalt nitrate hexahydrate to the zinc nitrate hexahydrate is 2-8:2-8.

[0011] Furthermore, based on the cobalt element in the cobalt nitrate hexahydrate and the zinc element in the zinc nitrate hexahydrate, the molar ratio of the cobalt nitrate hexahydrate to the zinc nitrate hexahydrate is 6-8:2-4.

[0012] Furthermore, based on the cobalt element in the cobalt nitrate hexahydrate and the zinc element in the zinc nitrate hexahydrate, the molar ratio of the cobalt nitrate hexahydrate to the zinc nitrate hexahydrate is 6:4.

[0013] Furthermore, in the solution containing cobalt nitrate hexahydrate and zinc nitrate hexahydrate, the total molar concentration of cobalt nitrate hexahydrate and zinc nitrate hexahydrate is 1.8 mmol / 15 mL, calculated based on the zinc element in zinc nitrate hexahydrate and the cobalt element in cobalt nitrate hexahydrate.

[0014] Furthermore, the volume ratio of the 2-methylimidazole solution to the solution containing cobalt nitrate hexahydrate and zinc nitrate hexahydrate is 5:3.

[0015] Furthermore, the preparation method of the solution containing cobalt nitrate hexahydrate and zinc nitrate hexahydrate is specifically as follows: dissolving and dispersing cobalt nitrate hexahydrate and zinc nitrate hexahydrate in deionized water.

[0016] Furthermore, there are many ways to mix evenly, such as stirring. To promote even mixing, those skilled in the art may stir for 1.5h-2.5h.

[0017] Furthermore, the standing time is 23h-25h.

[0018] Furthermore, the specific method of washing is: washing with ethanol and deionized water in sequence, washing at least 3 times.

[0019] Furthermore, the drying is specifically: vacuum drying is performed at 55° C.-65° C. for 11 h-13 h.

[0020] Furthermore, the calcination temperature is 850°C-950°C, and the calcination time is 1.5h-2.5h.

[0021] Furthermore, the heating rate to reach the calcination temperature is 1.5°C / min-2.5°C / min.

[0022] Furthermore, the inert atmosphere includes nitrogen.

[0023] The present invention also provides the use of the Co-doped porous carbon material derived from the Co-Zn bimetallic ZIFs in the degradation of chloramphenicol.

[0024] Furthermore, the dosage of the porous carbon material is 0.1 g / L, and the content of chloramphenicol is 1.0 mmol / L.

[0025] The embodiments of the present invention have the following technical effects: 1. In the porous carbon material of the present invention, the elemental cobalt and monatomic cobalt contained therein serve as active sites for the porous carbon material to catalyze peroxymonosulfate, thereby improving the catalytic activity of the porous carbon material; and the porous carbon material and the carbon nanotubes loaded on its surface provide a defective carbon structure, thereby further improving the catalytic activity of the porous carbon material.

[0026] 2. In the preparation method of the present invention, a bimetallic organic framework structure containing cobalt and zinc is first prepared, and then calcined and carbonized to form the porous carbon material of the present invention; first, cobalt can form elemental cobalt and single atomic cobalt during the calcination process, thereby providing active sites for activating peroxymonosulfate, and the incorporation of zinc is beneficial to the formation of a hierarchical porous carbon material structure after calcination; and zinc can volatilize during high-temperature calcination, on the one hand, forming carbon nanotubes on the surface of the porous carbon material, and on the other hand, promoting the formation of single atomic cobalt in the derived carbon material. It can be seen that the volatilization of zinc provides a defect structure for the carbon material.

[0027] 3. The content of cobalt and zinc is also designed in the present invention. On the basis of ensuring the stability of the porous carbon material structure in the present invention, the catalytic activity of the catalyst to peroxymonosulfate is further improved, and the effect of degrading chloramphenicol is achieved by catalyzing peroxymonosulfate to produce active oxygen. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0029] Figure 1 is a microscopic diagram provided by the embodiments and comparative examples of the present invention, wherein Figure 1 Figure a is a microscopic image of Co6Zn4-ZIF. Figure 1 b is the microscopic morphology of Example 1, Figure 1 Figure c is a microscopic morphology image of Example 1. Figure 1 d is the distribution diagram of each element in Example 1, Figure 1 e is the C element distribution diagram in Example 1, Figure 1 f is the N element distribution diagram in Example 1, Figure 1 g is the Co element distribution diagram in Example 1, Figure 1 h is the Zn element distribution diagram in Example 1.

[0030] Figure 2 is a TEM image of Example 1, wherein Figure 2 a is the TEM image of Example 1, Figure 2 b is the TEM image of Example 1, Figure 2 c is the microstructure of Example 1, Figure 2 d in the figure is the microstructure of Example 1, Figure 2 e is the lattice diagram of Example 1, Figure 2 In f, there is a lattice diagram of Example 1.

[0031] Figure 3 is the XRD diagram of the embodiment and the comparative example, wherein, Figure 3 a is the XRD diagram of the embodiment and the comparative example, Figure 3 b is the Roman diagram of the embodiments and comparative examples.

[0032] Figure 4 is a structural feature data diagram of the embodiments and comparative examples, wherein Figure 4 a in the figure is the nitrogen adsorption-desorption isotherm. Figure 4 b is the pore size distribution diagram of the embodiment and the comparative example.

[0033] Figure 5 is the XPS data diagram before and after catalysis of Example 1, wherein Figure 5 Where a is the element distribution in Example 1, Figure 5 b is the high-resolution spectrum of C 1s in Example 1, Figure 5 Where c is the high-resolution spectrum of N 1s in Example 1, Figure 5 (d) is the high-resolution spectrum of Co 2p in Example 1.

[0034] Figure 6 The degradation efficiency of chloramphenicol was evaluated by the embodiments and comparative examples, wherein Figure 6 a is the degradation capacity of chloramphenicol over time in the examples and comparative examples, Figure 6 b is a comparison of the reaction rate constants of the embodiment and the comparative example.

[0035] Figure 7 The impact test of degradation of chloramphenicol in Example 1, wherein Figure 7 Where a is the effect of the dosage of Example 1 on the degradation of chloramphenicol, Figure 7 Figure b shows the effect of peroxymonosulfate concentration on the degradation of chloramphenicol.

[0036] Figure 8 This is the effect of environmental pH on the degradation of chloramphenicol in Example 1.

[0037] Fig. 9 The purpose is to explore the mechanism of chloramphenicol degradation by catalyst. Fig. 9 a is the effect of different quenchers on the degradation of chloramphenicol. Fig. 9 b is the EPR spectrum of DMPO. Fig. 9 c is the EPR spectrum of TEMP, Fig. 9 Middle (d) is the result of quenching experiment.

[0038] Fig.10 is the stability test result of Example 1, wherein Fig.10 a in the figure is the result of the catalyst removing chloramphenicol over the time of introduction. Fig.10 (b) is the efficiency of the catalyst in degrading chloramphenicol at different cycle numbers. DETAILED DESCRIPTION

[0039] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.

[0040] In a first aspect, the present invention provides a Co-doped porous carbon material derived from Co-Zn bimetallic ZIFs, wherein the porous carbon material is doped with elemental cobalt and monatomic cobalt; and the surface of the porous carbon material has carbon nanotubes.

[0041] In the product of the present invention, elemental cobalt and single atomic cobalt serve as active sites for catalyzing chloramphenicol in porous carbon materials, thereby improving the catalytic activity of porous carbon materials; and the porous carbon materials and carbon nanotubes loaded on their surfaces provide defective carbon structures, thereby further improving the catalytic activity of the porous carbon materials.

[0042] In a second aspect, some embodiments of the present invention also provide a method for preparing a Co-doped porous carbon material derived from a Co-Zn bimetallic ZIFs, the preparation method comprising: Step S1: adding a 2-methylimidazole solution to a solution containing cobalt nitrate hexahydrate and zinc nitrate hexahydrate, mixing them evenly, standing them, separating the solid from the liquid, washing them, and drying them to obtain an intermediate product; Step S2: calcining the intermediate product under an inert gas atmosphere to obtain a porous carbon material.

[0043] In the method of the present invention, the formation of single atomic cobalt is facilitated by adjusting the zinc content and the heating rate of the calcination temperature.

[0044] In some embodiments, the molar concentration of the 2-methylimidazole solution is 22.05 mmol / 25 mL.

[0045] In some embodiments, the preparation method of the 2-methylimidazole solution is specifically: dissolving and dispersing 2-methylimidazole in deionized water.

[0046] In some embodiments, the molar ratio of the cobalt nitrate hexahydrate to the zinc nitrate hexahydrate is 2-8:2-8, calculated based on the cobalt element in the cobalt nitrate hexahydrate and the zinc element in the zinc nitrate hexahydrate.

[0047] In some embodiments, the molar ratio of the cobalt nitrate hexahydrate to the zinc nitrate hexahydrate is 6-8:2-4, calculated based on the cobalt element in the cobalt nitrate hexahydrate and the zinc element in the zinc nitrate hexahydrate.

[0048] In some embodiments, the molar ratio of the cobalt nitrate hexahydrate to the zinc nitrate hexahydrate is 6:4, calculated based on the cobalt element in the cobalt nitrate hexahydrate and the zinc element in the zinc nitrate hexahydrate.

[0049] In some embodiments, in the solution containing cobalt nitrate hexahydrate and zinc nitrate hexahydrate, the total molar concentration of cobalt nitrate hexahydrate and zinc nitrate hexahydrate is 1.8 mmol / 15 mL, calculated as zinc element in zinc nitrate hexahydrate and cobalt element in cobalt nitrate hexahydrate.

[0050] In some embodiments, the volume ratio of the 2-methylimidazole solution to the solution containing cobalt nitrate hexahydrate and zinc nitrate hexahydrate is 5:3.

[0051] In some embodiments, the method for preparing the solution containing cobalt nitrate hexahydrate and zinc nitrate hexahydrate is specifically as follows: dissolving and dispersing cobalt nitrate hexahydrate and zinc nitrate hexahydrate in deionized water.

[0052] In some embodiments, there are multiple ways to achieve uniform mixing, such as stirring. To promote uniform mixing, those skilled in the art may stir the mixture for a period of 1.5 h to 2.5 h.

[0053] In some embodiments, the standing time is 23h-25h.

[0054] In some embodiments, the specific method of washing is: washing with ethanol and deionized water in sequence, washing at least 3 times.

[0055] In some embodiments, the drying is specifically: vacuum drying at 55° C.-65° C. for 11 h-13 h.

[0056] In some embodiments, the calcination temperature is 850° C.-950° C., and the calcination time is 1.5 h-2.5 h.

[0057] In some embodiments, the heating rate to reach the calcination temperature is 1.5°C / min-2.5°C / min.

[0058] In some embodiments, the inert atmosphere includes nitrogen.

[0059] In a third aspect, some embodiments of the present invention also provide the use of the Co-doped porous carbon material derived from the Co-Zn bimetallic ZIFs in the degradation of chloramphenicol.

[0060] In some embodiments, the amount of the porous carbon material is 0.1 g / L, and the content of chloramphenicol is 1.0 mmol / L.

[0061] The following specific examples and comparative examples are described: Embodiment 1: 1.81 g of 2-methylimidazole (22.05 mmol) was dissolved in 25 mL of deionized water under ultrasound, and the solution was recorded as solution A. Then 314.32 mg of cobalt nitrate hexahydrate (1.08 mmol) and 214.19 mg of zinc nitrate hexahydrate (0.72 mmol) were dissolved in 15 mL of deionized water, wherein the total molar amount of cobalt nitrate hexahydrate and zinc nitrate hexahydrate was 1.8 mmol, and after being fully mixed, it was recorded as solution B. Then, solution A was slowly added to solution B under continuous stirring, and the two solutions were mixed and stirred continuously for 2 hours and then allowed to stand for 24 hours. Subsequently, the solid product was collected by centrifugation, and then repeatedly washed with ethanol and deionized water for at least 3 times, and a purple product was obtained after vacuum drying at 60 ° C for 12 hours, named Co6Zn4-ZIF; The prepared Co6Zn4-ZIF was placed in a corundum crucible boat and pyrolyzed at 900°C for 2 hours at a heating rate of 2°C / min in a nitrogen environment to obtain a porous carbon material, which was recorded as: Co6Zn4-NC.

[0062] Embodiment 2: 1.81 g of 2-methylimidazole (22.05 mmol) was dissolved in 25 mL of deionized water under ultrasound, and the solution was recorded as solution A. Then 1.44 mmol of cobalt nitrate hexahydrate and 0.36 mmol of zinc nitrate hexahydrate were dissolved in 15 mL of deionized water, wherein the total molar amount of cobalt nitrate hexahydrate and zinc nitrate hexahydrate was 1.8 mmol, and after being fully mixed, it was recorded as solution B. Then, solution A was slowly added to solution B under continuous stirring, and the two solutions were mixed and stirred for 2 hours and then allowed to stand for 24 hours. Subsequently, the solid product was collected by centrifugation, and then repeatedly washed with ethanol and deionized water for at least 3 times, and a purple product was obtained after vacuum drying at 60 ° C for 12 hours, named Co8Zn2-ZIF; The prepared Co8Zn2-ZIF was placed in a corundum crucible boat and pyrolyzed at 900°C for 2 hours at a heating rate of 2°C / min in a nitrogen environment to obtain a porous carbon material, which was recorded as: Co8Zn2-NC.

[0063] Embodiment 3: 1.81 g of 2-methylimidazole (22.05 mmol) was dissolved in 25 mL of deionized water under ultrasound, and the solution was recorded as solution A. Then 0.72 mmol of cobalt nitrate hexahydrate and 1.08 mmol of zinc nitrate hexahydrate were dissolved in 15 mL of deionized water, wherein the total molar amount of cobalt nitrate hexahydrate and zinc nitrate hexahydrate was 1.8 mmol, and after being fully mixed, it was recorded as solution B. Then, solution A was slowly added to solution B under continuous stirring, and the two solutions were mixed and stirred for 2 hours and then allowed to stand for 24 hours. Subsequently, the solid product was collected by centrifugation, and then repeatedly washed with ethanol and deionized water for at least 3 times, and a purple product was obtained after vacuum drying at 60 ° C for 12 hours, named Co4Zn6-ZIF; The prepared Co4Zn6-ZIF was placed in a corundum crucible boat and pyrolyzed at 900°C for 2 hours at a heating rate of 2°C / min in a nitrogen environment to obtain a porous carbon material, which was recorded as: Co4Zn6-NC.

[0064] Embodiment 4: 1.81 g of 2-methylimidazole (22.05 mmol) was dissolved in 25 mL of deionized water under ultrasound, and the solution was recorded as solution A. Then, 0.36 mmol of cobalt nitrate hexahydrate and 1.44 mmol of zinc nitrate hexahydrate were dissolved in 15 mL of deionized water, wherein the total molar amount of cobalt nitrate hexahydrate and zinc nitrate hexahydrate was 1.8 mmol, and after being fully mixed, it was recorded as solution B. Then, solution A was slowly added to solution B under continuous stirring, and the two solutions were mixed and stirred continuously for 2 hours and then allowed to stand for 24 hours. Subsequently, the solid product was collected by centrifugation, and then repeatedly washed with ethanol and deionized water for at least 3 times, and a purple product was obtained after vacuum drying at 60 ° C for 12 hours, named Co2Zn8-ZIF; The prepared Co2Zn8-ZIF was placed in a corundum crucible boat and pyrolyzed at 900°C for 2 hours at a heating rate of 2°C / min in a nitrogen environment to obtain a porous carbon material, which was recorded as: Co2Zn8-NC.

[0065] Comparative Example 1: 1.81 g of 2-methylimidazole (22.05 mmol) was dissolved in 25 mL of deionized water under ultrasound, and the solution was recorded as solution A. 1.8 mmol of cobalt nitrate hexahydrate was dissolved in 15 mL of deionized water and recorded as solution B after being fully mixed. Then, solution A was slowly added to solution B under continuous stirring, and the two solutions were mixed and stirred for 2 hours and then allowed to stand for 24 hours. Subsequently, the solid product was collected by centrifugation, and then repeatedly washed with ethanol and deionized water for at least 3 times, and dried in vacuum at 60 ° C for 12 hours to obtain a purple product, named ZIF-67; The prepared ZIF-67 was placed in a corundum crucible boat and pyrolyzed at 900°C for 2 hours at a heating rate of 2°C / min in a nitrogen environment to obtain a porous carbon material, which was recorded as: Co-NC.

[0066] Comparative Example 2: 1.81 g of 2-methylimidazole (22.05 mmol) was dissolved in 25 mL of deionized water under ultrasound, and the solution was recorded as solution A. 1.8 mmol of zinc nitrate hexahydrate was dissolved in 15 mL of deionized water and recorded as solution B after being fully mixed. Then, solution A was slowly added to solution B under continuous stirring, and the two solutions were mixed and stirred for 2 hours and then allowed to stand for 24 hours. Subsequently, the solid product was collected by centrifugation, and then repeatedly washed with ethanol and deionized water for at least 3 times, and dried in vacuum at 60 ° C for 12 hours to obtain a purple product, named ZIF-8; The prepared ZIF-8 was placed in a corundum crucible boat and pyrolyzed at 900°C for 2 hours at a heating rate of 2°C / min in a nitrogen environment to obtain a porous carbon material, which was recorded as: Zn-NC.

[0067] The following examples and comparative examples were tested: The degradation experiments were carried out in a 250 mL beaker with continuous stirring at room temperature (25 ± 1 °C). Typically, the experimental solution was mixed with 100 mL of reaction solution (CAP: 20 mg / L) and 10 mg of catalyst. After stirring for 30 min, 10 mg of PMS was added to the solution to start the degradation reaction. After adding PMS, the initial pH of the system was adjusted with NaOH solution (0.1 mmol) and controlled with 10 mmol borate buffer. During the reaction, 1 mL of sample was taken from the experimental solution at regular intervals and filtered with a 0.22 μm nylon membrane filter to remove the catalyst. Then an equal volume of methanol was immediately injected into the solution sample to quench the reaction.

[0068] The concentration of chloramphenicol in the solution at different times was monitored using high performance liquid chromatography (HPLC, UltiMateTM3000, Japan) equipped with a C18 column (4.6 mm × 250 mm × 5 μm) and a UV detector at a wavelength of 277 nm. The mobile phase was equal amounts of acetonitrile and water (60:40, v / v) with a flow rate of 1.0 mL / min.

[0069] Results and analysis: Table 1 Specific surface area, pore solution and average pore diameter of the examples and comparative examples

[0070] A catalyst is successfully obtained through the method of the present invention. In the present invention, cobalt can form elemental cobalt and single atomic cobalt during the calcination process, thereby providing active sites for catalyzing peroxymonosulfate, and zinc can not only form a bimetallic organic framework structure with cobalt, which is beneficial to the formation of a porous carbon material structure after calcination; zinc can also volatilize during calcination, forming carbon nanotubes on the surface of the porous carbon material on the one hand, and forming a porous structure in the formed carbon material on the other hand. It can be seen that the volatilization of zinc provides a defective structure for the carbon material; in addition, the addition of zinc is beneficial to the formation of single atomic cobalt. When the zinc content increases, although it will enhance the defective structure of the carbon material, it will also cause poor structural stability and structural collapse. When the zinc content is low, less defective carbon material for catalysis is generated in the porous carbon material, which is not conducive to catalyzing peroxymonosulfate and degrading chloramphenicol. Figure 4 As shown in Figure 1, we further evaluated the structural characteristics of these catalysts using N2 adsorption-desorption isotherms. All six catalysts showed typical IV isotherms accompanied by H4-type hysteresis loops, indicating that both micropores and mesopores exist in all catalyst structures. Table 1 summarizes the specific surface area, pore size, and pore volume of all six catalysts. It can be found that with the increase of Co x Zn 10-x -NC precursor with an increase in Zn content, the obtained Co x Zn 10-x -NC also gradually increases in specific surface area and pore volume, while the average pore size gradually decreases. This may be due to the increase in Zn content, the components volatilized during the calcination process also increase, and more cavities and carbon nanotube structures are generated in this process, which gradually increases the pore volume of the catalyst, and at the same time, the structural collapse caused by the volatilization of Zn during calcination is more serious. Therefore, in the present invention, the molar ratio of the cobalt element in the hexahydrate cobalt nitrate and the zinc element in the hexahydrate zinc nitrate is 2-8:2-8.

[0071] On this basis, further research on Co x Zn 10-x The catalytic activity of -NC was evaluated by the CAP degradation efficiency in different reaction systems. Except for the type of catalyst, other reaction conditions remained unchanged. Figure 6 As shown in (a), the six catalysts prepared in the present invention can degrade CAP to a certain extent within one hour. The catalytic activity of the catalysts is significantly improved when Zn is added, and reaches the highest when the Co:Zn ratio is 6:4. The reaction system with Co6Zn4-NC as the catalyst can completely remove CAP in the solution within 60 minutes. By further calculating the reaction rate constant kapp, the catalytic activity of the catalysts can be more clearly compared. Figure 6As shown in (b), the maximum reaction rate constant kapp of Co6Zn4-NC within 15 min is 0.22 min -1 The reaction rate constant kapp of Co8Zn2-NC within 15 min is second, which is significantly higher than the reaction rate constant kapp of Co-NC derived from single metal ZIF-67(Co) (0.11 min -1 ), which indicates that proper Zn incorporation can effectively improve the x Zn 10-x -NC catalytic activity, combined with the above characterization, this may be due to the large number of carbon nanotubes formed on the catalyst surface, and the Co atoms in the form of single atoms. Therefore, it is further preferred that the molar ratio of cobalt nitrate hexahydrate to zinc nitrate hexahydrate is 6-8:2-4, based on the cobalt element in cobalt nitrate hexahydrate and the zinc element in zinc nitrate hexahydrate. However, with the further increase of Zn content, the reaction rate of the reaction system increases from 0.22min -1 Significantly reduced to 0.06min -1 , which may be due to the large reduction in the content of Co as the main active site in the catalyst structure. In addition, the total organic carbon concentration (TOC) can, to a certain extent, explain the ability of the reaction system to completely mineralize CAP into carbon dioxide and water. It can be observed that the reaction system with Co6Zn4-NC as the catalyst has the strongest mineralization ability, and 44.57% of CAP was mineralized within 60 minutes, which is much higher than 36.11% of Co-NC and 25.32% of Zn-NC. In summary, among the catalysts prepared in this study, Co6Zn4-NC exhibits the highest catalytic activity. It is further preferred that the molar ratio of cobalt nitrate hexahydrate to zinc nitrate hexahydrate is 6:4, based on the cobalt element in cobalt nitrate hexahydrate and the zinc element in zinc nitrate hexahydrate. Therefore, subsequent experiments will also be conducted based on Co6Zn4-NC for further research.

[0072] Taking the example Co6Zn4-NC as an example, the SEM images of Co6Zn4-ZIF and Co6Zn4-NC are as follows: Figure 1 First, from Figure 1 (a) It can be observed that Co6Zn4-ZIF exhibits a typical rhombic dodecahedron morphology, which is similar to the morphology of single metal ZIF-8 and ZIF-67 reported in the literature (The preparation of Ag-ZIF-8@ZIF-67 core-shell composites as excellent catalysts for degradation of the nitroaromatic compounds[J]. Applied Surface Science, 2020, 516: 146160), which indicates that the co-existence of the two metal elements will not have a significant effect on the micromorphology of the metal-organic framework structure. Figure 1 (b) and Figure 1 (c) shows the microstructure of the Co6Zn4-NC obtained after calcination. Its average particle diameter is significantly reduced from 2-3μm before calcination to 0.8-1μm after calcination. The smooth surface becomes rough after calcination and a large number of fibrous structures appear. This may be due to the volatilization of zinc metal nanoparticles during the calcination process, causing the collapse and shrinkage of the Co6Zn4-ZIF structure. The large number of fibrous structures appearing on the surface of Co6Zn4-NC may be the carbon nanotube structure produced by the high-temperature volatilization of Zn during the calcination process. On this basis, we characterized the element distribution of Co6Zn4-NC through elemental mapping analysis, and the results observed are as follows: Figure 1 (d)-1(h). It can be found that in Co6Zn4-NC, C, N, Co and Zn are evenly distributed in the material, and there is still a small amount of Zn (0.98%) which may be attributed to incomplete calcination, while the contents of Co and N are 27.02% and 2.43%, respectively.

[0073] Figure 2 The microstructural characteristics of Co6Zn4-NC obtained by TEM characterization. Figure 2 (a) and Figure 2 As shown in (b), a large number of black nanoparticles are distributed inside the Co6Zn4-NC, which may be the Co-based metal nanoparticles formed by Co metal clusters during the calcination process. Figure 2 (c) further shows the microstructure of the fibrous structure on the surface of Co6Zn4-NC, which is mainly a hollow tubular structure, which may be formed by the volatilization of Zn during the calcination process. As the structure inside Co6Zn4-NC is further magnified, it can be seen from Figure 2 In (d), it is observed that the metal nanoparticles inside the structure are all wrapped in a dense structure. Figure 2 The lattice fringes in (e) show that the metal nanoparticles show a lattice fringes d1 of 0.204nm, which belongs to the (111) crystal plane of the metal Co nanoparticles (PDF#15-0806). This proves to a certain extent that Co exists in the form of metal Co after calcination; and the dense structure around the Co nanoparticles shows a lattice spacing d2 of 0.34nm, which is consistent with the (002) crystal plane of graphite carbon (PDF#41-1487). This should be the result of Co catalyzing carbon graphitization, indicating that the Co nanoparticles in the Co6Zn4-NC structure are covered by dense graphite carbon structures. At the same time, we also analyzed the nanotube structure on the surface. Figure 2 (f) It can be observed that the lattice spacing d3 of the tubular structure is also 0.34nm, which indicates that these structures are carbon nanotube structures. During the pyrolysis process, these randomly oriented graphitized carbon structures are coated on the surface of the larger Zn nanoparticles, and as the temperature rises, the Zn nanoparticles begin to gasify and move, resulting in the formation of these graphitized carbon tubes on the surface.

[0074] Figure 3 (a) is Co x Zn 10-x -NC, Co-NC and Zn-NC XRD characterization results are shown in the figure. x Zn 10-x In the XRD patterns of -NC and Co-NC, a broad and weak peak at 26.13° and two sharp and high-intensity characteristic peaks at 44.35° and 51.66° can be observed. The characteristic peak at 26.13° corresponds to the (002) crystal plane of graphitic carbon (PDF#41-1487), which is consistent with the interplanar spacing observed by high-resolution TEM characterization. The two peaks at 44.35° and 51.66° are respectively attributed to the (111) crystal plane and (200) crystal plane of metallic Co crystal (PDF#15-0806), of which the (111) crystal plane is also observed in TEM characterization. In addition, it can be observed that with the increase of Co x Zn 10-x -NC precursors gradually increase the proportion of Zn, Co x Zn 10-x The intensity of the two characteristic peaks at 44.35° and 51.66° in Zn-NC also gradually decreased, which may be attributed to the reduction of Co content in the structure or the reduction of the size of metal Co particles. When the calcined MOFs structure does not contain Co, the characteristic peaks corresponding to Co in the obtained Zn-NC structure disappear, and are replaced by two high-intensity broad characteristic peaks at 26.13° and 43.95°, which can indicate the presence of disordered and defective carbon structures in the material (PDF#41-1487). Figure 3 (b) shows the Raman spectra of different catalysts. As shown in the figure, different catalysts have the same Raman spectrum at 1342 cm -1 and 1589cm -1There are two characteristic peaks nearby, which are attributed to the stretching vibration of the sp2-hybridized carbon network of disordered carbon (D band) and graphitized carbon (G band). The degree of graphitization of the catalyst can be evaluated by calculating the ratio of disordered carbon to graphitized carbon (ID / IG). After calculation, the values ​​of ID / IG of six different catalysts are 2.59, 2.53, 4.98, 4.034, 4.055 and 4.47, respectively. Among them, the relative intensity of ID / IG of Co6Zn4-NC is higher than that of the other five catalysts, which indicates that Co6Zn4-NC has the highest degree of defects and can provide more active sites for the reaction during the reaction, thereby improving its catalytic performance.

[0075] like Figure 5 As shown in Figure 2, the XPS test characterized the changes in the valence state of the surface elements before and after the catalyst reaction. Figure 5 As shown in (a), there are C, N, O, and Co elements on the catalyst surface, while Zn is almost not observed, which is similar to the results obtained by element mapping. It is worth noting that the intensity of the four main elements has hardly changed before and after the reaction, which to some extent indicates that there is less ion leaching during the reaction and the catalyst is more stable. Figure 5 (b) shows the high-resolution spectrum of C 1s. The C 1s spectrum can be decomposed into three characteristic peaks at 284.8 eV, 285.8 eV and 289.3 eV by fitting, corresponding to the CC bond, CO bond and C=O bond in the catalyst, respectively. This is similar to the carbon composition in the transition metal-carbon materials derived from MOFs reported previously (Trimetallic MOFs-derived Fe-Co-Cu oxycarbidetoward peroxymonosulfate activation for efficient trichlorophenol degradationvia high-valent metal-oxo species[J]. Chemical Engineering Journal , 2023, 468:143444.). Figure 5 (d) shows the XPS spectrum of Co 2p, which can be decomposed into three peaks, which are respectively attributed to Co 0 (778.5eV)、Co 3+ (780.2eV) and Co 2+ (782.0eV). Different from the XRD and TEM characterization results, Co in the material exists not only in the form of zero valence, but also in the form of Co 3+ and Co 2+, and no corresponding cobalt oxides were found in previous tests. This may be because during the calcination process, due to the presence of Zn, part of the Co is isolated and coordinated with N, thus forming single atomic cobalt, while the other part of the agglomerated Co atoms coordinate with the Co atoms themselves to form metallic Co nanoparticles. To further prove this speculation, we further analyzed the XPS high-resolution spectrum of N. As the main active substance second only to the metal center, N plays a vital role in the coordination with metal atoms. Various types of N have completely different electronic structures and catalytic properties. Figure 5 (c) shows the high-resolution spectrum of N 1s, which can be decomposed into graphitized N (401.3 eV), pyrrolidine N (399.7 eV), pyridine N (398.6 eV) and Co-N (399.0 eV) after fitting. As we speculated, pyrrolidine N dominated the coordination with Co atoms during the calcination process to form single-atom Co. We analyzed the surface element valence state of the Co6Zn4-NC structure after the reaction by XPS characterization, such as Figure 5 As shown in (c), N is an important active site second only to Co. Pyridine N (398.6 eV) decreased from 8.1% before the reaction to 5.6%, Co-N (399.0 eV) decreased from 24.2% before the reaction to 14.7%, while graphitized N (401.3 eV) and pyrrolidine N (399.7 eV) showed an upward trend, indicating that pyridine N and Co-N are possible active sites. In addition, Figure 5 (d) also shows that after the reaction, Co 2+ (782.0eV) decreased significantly from 34.2% to 22.7%, and the corresponding Co 3+ (780.2eV) increased from 28.1% to 33.3%, indicating that Co is the most important active site in the material.

[0076] PMS (permonosulfate) concentration, catalyst dosage and initial pH value always have a significant impact on the degradation efficiency of pollutants in the PMS-based SR-AOPs system. Figure 7 (a) shows that as the catalyst dosage increases from 0.05 g / L to 0.1 g / L, the degradation efficiency of CAP (chloramphenicol) in the Co6Zn4-NC+PMS system has been significantly improved. This is mainly because the larger the catalyst dosage, the more active sites that catalyze the self-decomposition of PMS, thereby promoting the generation of ROS (reactive oxygen species), and ultimately improving the degradation ability of the reaction system to CAP. However, as the catalyst dosage is further increased from 0.1 g / L to 0.25 g / L, the degradation efficiency of CAP in the Co6Zn4-NC+PMS system did not show a significant improvement, and even remained unchanged. This may be due to the excess Co in the reaction system. 2+A portion of sulfate radicals and hydroxyl radicals are consumed. Figure 7 (b) shows the effect of PMS dosage on CAP degradation efficiency in the Co6Zn4-NC+PMS system. As shown in the figure, when the concentration of PMS increased from 0.5mmol / L to 1.0mmol / L, the CAP removal rate increased significantly from 92.4% to 100%, and the corresponding reaction rate constant also increased from 0.15min to 1.0min. - 1 rises to 0.22min -1 , which shows that the increase of PMS dosage has a significant promoting effect on the Co6Zn4-NC+PMS system. However, with the further increase of PMS dosage, the catalytic performance of the Co6Zn4-NC+PMS system has not been significantly improved. This may be because the limited catalyst in the reaction system is not enough to provide enough active sites for the excess PMS at the same time, and this will also cause some PMS to self-quench. Therefore, here we choose 0.1g / L Co6Zn4-NC and 1.0mmol / L PMS as the optimal parameters of the experiment.

[0077] In the Co6Zn4-NC+PMS system, the initial pH value of the reaction will indirectly affect the charge of the catalyst surface and the activity of the reaction sites, so it is very important for the removal of CAP. Figure 8 As shown in the figure, the Co6Zn4-NC+PMS system exhibited the highest catalytic activity at pH 7, and the catalytic activity of the Co6Zn4-NC+PMS system was similar at pH 9 and was not significantly affected. However, at pH 3 and 5, the removal rate of CAP in the reaction system dropped significantly to 71.9% and 94.1%, and the corresponding reaction rate constant also dropped from 0.22 min to 1.54 min. -1 Reduced to 0.05min -1 and 0.13min -1 This may be due to the presence of a large amount of H + It not only quenches some ROS generated by the self-decomposition of PMS, but also competes with Co6Zn4-NC for the OO bond of PMS, thereby hindering the self-decomposition of PMS activated by Co6Zn4-NC. When the pH value of the Co6Zn4-NC+PMS system increases to 11, the removal rate of CAP drops to the minimum, and only 50.4% of CAP is removed at 60 minutes, and the corresponding reaction rate constant is significantly reduced to 0.02min -1 This may be because Co(OH)2 precipitates with low catalytic activity were formed under alkaline conditions. In summary, the optimal reaction pH value of the Co6Zn4-NC+PMS system should be 7.

[0078] In order to study the potential reaction mechanism of the Co6Zn4-NC+PMS system, we first need to determine the ROS generated by the activation of PMS by Co6Zn4-NC. For this purpose, we conducted a free radical quenching experiment. Since free radicals and non-free radicals may exist simultaneously in the catalyst+PMS system, methanol (MeOH) was selected as the hydroxyl radical (•OH) and sulfate radical (SO4 •– ) scavenger, tert-butyl alcohol (TBA) was selected as the quencher of •OH, and furfuryl alcohol (FFA) was selected as the singlet oxygen ( 1 O2) scavenger, p-benzoquinone (p-BQ) was selected as the superoxide radical (O2 •– ) scavenger. Fig. 9 As shown in (a), in the presence of ultra-high concentration of MeOH (1000 mM), the removal efficiency of CAP decreased significantly from 100% to 29.4%, indicating that the free radical pathway is the main pathway for PMS activation in the Co6Zn4-NC+PMS system, while •OH and SO4 •– It is the main ROS for CAP degradation. We further confirmed the main free radical species by TBA, and observed that in the presence of 1000mM TBA, the removal rate of CAP was 74.4%, which indicates that among the two free radicals, SO4 •– The contribution of •OH to CAP degradation was greater, while •OH also played a certain role in degradation. In the presence of 50 mM FFA, the removal rate of CAP decreased by 13.2%, which indicates that 1 O2 may also play a role in the degradation of CAP, but it is not the main ROS. •– It may be an intermediate product in the reaction process of the SR-AOPs system and can be converted into 1 O2, due to 1 O2 has a certain contribution to the degradation of CAP, so we studied the effect of O2 by adding p-BQ. •– However, in the presence of 10 mM p-BQ, the removal rate of CAP decreased by only 1.9%, which was almost negligible, indicating that O2 •– There is no significant contribution to the location of CAP, and O2 •– Not a small amount 1 The source of O2.

[0079] On this basis, we tested the types of ROS generated by PMS self-degradation through EPR characterization. Fig. 9As shown in (b), the Co6Zn4-NC+PMS system shows a high-intensity signal attributed to 5,5-dimethyl-1-pyrroline-N-oxide (DMPO-X) (1:2:1:2:1:2:1:2:1), and the intensity of the signal increases significantly from 5 min to 10 min, indicating that •OH and SO4 are produced during the reaction. •– , and continues to be generated as the reaction proceeds. Fig. 9 (c) shows a weaker atom attributable to 2,2,6,6-tetramethylpiperidinyloxide (TEMP- 1 O2)(1:1:1), but its intensity is weaker than that of DMPO-X, and its signal intensity does not change significantly as the reaction proceeds. Fig. 9 (d) confirms the results of the quenching experiment, and there is almost no O2 in the reaction process •– The production of.

[0080] The stability of the catalyst is one of the important indicators for evaluating the performance of the catalyst. Therefore, we collected the catalyst after CAP degradation, washed and dried it, and reused it five times under the same experimental conditions. At the same time point, the removal efficiency of CAP in the Co6Zn4-NC+PMS system was tested. Fig.10 As shown. Fig.10 As shown in (b), the removal efficiency of CAP did not change significantly in the first two cycles, while the removal rate of CAP slightly decreased to 98.1% in the third cycle. In the fourth cycle, the removal rate of CAP decreased to 92.6% and further decreased to 88.7% in the fifth consecutive cycle, which was mainly due to the leaching of Co ions during the reaction, resulting in a reduction in active sites. In addition, the organic matter adsorbed on the catalyst surface during multiple cycles may also reduce the exposed active sites, resulting in a decrease in the removal rate of CAP. In summary, after five cycles, the Co6Zn4-NC+PMS system was still able to remove 88.7% of CAP within 60 minutes, and Co6Zn4-NC showed good stability and reusability.

[0081] It should be noted that the terms used in the present invention are only for describing specific embodiments, rather than limiting the scope of the present application. As shown in the present specification, unless the context clearly indicates an exception, the words "one", "a", "a kind of" and / or "the" do not specifically refer to the singular, but may also include the plural. The terms "include", "comprise" or any other variant thereof are intended to cover non-exclusive inclusion, so that the process, method or device including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method or device. In the absence of more restrictions, the elements defined by the sentence "include one..." do not exclude the presence of other identical elements in the process, method or device including the elements.

[0082] It should also be noted that the orientations or positional relationships indicated by the terms "center", "up", "down", "left", "right", "vertical", "horizontal", "inside", "outside", etc. are based on the orientations or positional relationships shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention. Unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", etc. should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be an indirect connection through an intermediate medium, or it can be a connection between the two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0083] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the technical solutions of the embodiments of the present invention.

Claims

1. A Co-doped porous carbon material derived from Co-Zn bimetallic ZIFs, characterized in that: The porous carbon material is doped with single substance cobalt and single atomic cobalt; and the surface of the porous carbon material has carbon nanotubes.

2. The method for preparing the Co-doped porous carbon material derived from the Co-Zn bimetallic ZIFs according to claim 1, characterized in that: The preparation method comprises: Step S1: adding a 2-methylimidazole solution to a solution containing cobalt nitrate hexahydrate and zinc nitrate hexahydrate, mixing them evenly, standing them, separating the solid from the liquid, washing them, and drying them to obtain an intermediate product; Step S2: calcining the intermediate product under an inert gas atmosphere to obtain a porous carbon material.

3. The preparation method according to claim 2, characterized in that: The molar concentration of the 2-methylimidazole solution is 22.05 mmol / 25 mL.

4. The preparation method according to claim 2, characterized in that: The molar ratio of the cobalt nitrate hexahydrate to the zinc nitrate hexahydrate is 2-8:2-8, calculated based on the cobalt element in the cobalt nitrate hexahydrate and the zinc element in the zinc nitrate hexahydrate.

5. The preparation method according to claim 2, characterized in that: Calculated based on the zinc element in zinc nitrate hexahydrate and the cobalt element in cobalt nitrate hexahydrate, the total molar concentration of cobalt nitrate hexahydrate and zinc nitrate hexahydrate in the solution containing cobalt nitrate hexahydrate and zinc nitrate hexahydrate is 1.8 mmol / 15 mL.

6. The preparation method according to claim 2, characterized in that: The volume ratio of the 2-methylimidazole solution to the solution containing cobalt nitrate hexahydrate and zinc nitrate hexahydrate is 5:

3.

7. The preparation method according to claim 2, characterized in that: The standing time is 23h-25h.

8. The preparation method according to claim 2, characterized in that: The drying is specifically: vacuum drying at 55°C-65°C for 11h-13h; The calcination temperature is 850° C.-950° C., and the calcination time is 1.5 h-2.5 h.

9. The preparation method according to claim 8, characterized in that: The heating rate to reach the calcination temperature is 1.5°C / min-2.5°C / min.

10. Use of the Co-doped porous carbon material derived from the Co-Zn bimetallic ZIFs according to claim 1 or the Co-doped porous carbon material derived from the Co-Zn bimetallic ZIFs obtained by the preparation method according to any one of claims 2 to 9 in the degradation of chloramphenicol.

Citation Information

Cited By

  • Preparation method and application of porous core-shell iron-nitrogen-carbon catalyst

    CN121082307A

  • CoZn bimetallic catalyst and preparation method and application thereof

    CN122209396A